2018
DOI: 10.1111/and.13080
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sperm function and structure after freezing in domestic cat spermatozoa

Abstract: Sperm cryopreservation allows for a long-term storage of genetic. However, changes due to factors as cold shock, osmotic and oxidative stress cause reduction in viability and fertilising ability of frozen/thawed spermatozoa. Therefore, evaluation of cryoinjury of cat spermatozoa is a key factor in achieving better cryopreservation results. This study analysed the changes in structural and functional after freezing in ejaculated domestic cats spermatozoa. Semen samples (n = 60) were analysed before and after fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 56 publications
0
7
0
1
Order By: Relevance
“…Furthermore, it is important to consider that mitochondria, located in the midpiece region, are the organelles responsible for producing energy for the flagellar movement of the sperm cells and that this activity decreases when the cells are cryopreserved. (Cheuquemán et al, 2018). Consequently, morphometry can be a low-cost method for evaluating cryopreservation efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it is important to consider that mitochondria, located in the midpiece region, are the organelles responsible for producing energy for the flagellar movement of the sperm cells and that this activity decreases when the cells are cryopreserved. (Cheuquemán et al, 2018). Consequently, morphometry can be a low-cost method for evaluating cryopreservation efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, these studies were carried out with spermatozoa from the epididymis. Differences in the morphometric dimensions of fresh spermatozoa after thawing can be attributed to several events, including osmotic changes triggered by the progressive dehydration of these cells during the cryopreservation process (Cheuquemán et al., 2018; Martins & Justino, 2015), alterations in cellular compartments (Arruda et al., 2002), damage or loss of the sperm acrosome (Peña et al., 2003) and excess condensation of sperm chromatin (Álvarez et al., 2008). Considering these events, the extenders used in this experiment maintained the morphometric characteristics of the spermatozoa, except for the midpiece, which was lower in the extender with glycerol in 3% with 2% methylformamide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluating sperm parameters is fundamental to understand the extent of the damage caused to the spermatozoa during cryopreservation, as well as analyzing protocols and choosing diluents, and cryoprotectants to better protect the cell mechanisms (Cheuquemán et al, 2018). The present study showed that both external cryoprotectants (egg yolk and A. vera) maintained the sperm motility during cooling, independent of the concentration of A. vera used in the diluent; however, the sperm motility after thawing was similar between the diluents composed of egg yolk or A. vera, only when the plant extract was used in the same concentration of the usual extracellular cryoprotectant, indicating that a possible cryoprotective effect on feline sperm requires concentration above 10% of A. vera.…”
Section: Discussionmentioning
confidence: 99%
“…A criopreservação dos espermatozoides epididimários felinos apresenta protocolos diversificados, todavia, a preservação da motilidade pós-descongelação ainda é uma problemática (Kunkitti et al, 2017). Estudos futuros visando a compreensão da fisiologia espermática e as modificações estruturais/funcionais dos espermatozoides durante as etapas da criopreservação são necessários para minimizar as crinjurias (Cheuquemán et al, 2018). O entendimento dos fenômenos que envolve a teratozoospermia é uma lacuna que também deve ser investigada na espécie, para o melhor entendimento das diferenças metabólicas entre os gametas normais e anormais e futuramente, desenvolver protocolos específicos para animais únicos que apresentem elevadas taxas de espermatozoides pleimórficos (Terrel et al, 2010).…”
Section: Novas Perspectivasunclassified